Synthesis of novel 1, 2, 3-triazole based polycarboxylic acid functionalised ligands for MOF systems. Issue 6 (7th February 2019) - Belay, Yonas; Coetzee, Louis-Charl; Williams, D. Bradley G.; Muller, Alfred
Graphical abstract: Highlights: Click reactions produce polytopic triazole-carboxylic ligands. These ligands are potentially useful to produce MOFs. Most ligands are characterised by X-ray crystallography. One produces an interesting solid structure containing 1D, 2D and 3D features. Abstract: Copper catalysed click reactions are excellent tools to generate various 1, 2, 3-triazole linked polytopic aromatic carboxylates. The general reaction route involves protection of the carboxylates before proceeding with the click reaction. These polycarboxylate azoles are conveniently prepared for potential utility as novel key building blocks for metal organic frameworks. In one case, the ligand crystallises into a solid structure containing 1D, 2D and 3D features, based on a zigzag 1D structure, a 'chicken mesh'-like 2D structure and a 3D structure with very well-defined channels.